Anterior Cruciate Ligament Reconstruction in Pediatric and Adolescent Patients Using Quadriceps Tendon Autograft. Issue 4 (December 2016) - Albright, Jay; Lepon, Ariel Kiyomi; Mayer, Stephanie
Abstract : Many techniques for reconstruction of pediatric and adolescent anterior cruciate ligament (ACL) ruptures have been described, yet the best technique to reproduce normal kinematics of the knee while causing minimal growth disturbance is not definitively determined. We describe a technique which adapts the Allen Anderson technique for all-inside, all-epiphyseal, anatomic ACL reconstruction. However, this technique uses a novel quadriceps tendon—patellar bone—autograft to provide the best-possible patient outcomes. ACL reconstruction advancement in pediatrics is important as an increasing number of adolescent athletes experience ACL rupture and desire to return to sport.